THOUGHTS OF ISLAMIC RELIGIOUS EDUCATION TO RESPOND TO GLOBAL ETHICS, SOCIAL ETHICS AND HUMAN FRATERNITY - Naimi, Nadlrah; Amini, Nur Rahmah (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this research is to see the impact of technological advances and the times on the development of society, especially in the world of education. This research is a qualitative type through literature study with a content analysis approach. The stages of the research were carried out by collecting library sources, both primary and secondary. The results of the study show that negative impacts in the form of social conflict, corruption, acts of violence all have an impact on societal values. This also has an impact on the world of education where it is not uncommon for violence to occur in schools, student brawls, immoral acts and so on. Islamic religious education as a forum for forming students who have morality and noble character are required to be able to play a role with various concepts and thoughts that can at least minimize negative actions that can undermine social norms so that they can answer global ethical problems, ethics social and human fraternity.